Microbial Synthesis of Neo-Allo-Ocimene by Celery-Derived Neo-Allo-Ocimene Synthase - Zheng Liu; Ting Gao; Shaoheng Bao; Penggang Han; Ge Yao; Tianyu Song; Longbao Zhu; Chang Chen; Hui Jiang (Fermentation)
Neo-allo-ocimene is a monoterpene which could be applied in pesticides, fragrances, and sustainable polymers. In this study, we mined a terpene synthase, AgTPS40, from the transcriptome of celery leaf tissues. Through sequence and phylogenetic analysis, AgTPS40 was characterized as a monoterpene synthase. The AgTPS40 gene was introduced into a heterologous mevalonate pathway hosted in Escherichia coli to enable terpene production. Gas chromatography–mass spectrometry analysis confirmed that AgTPS40 catalyzes the formation of neo-allo-ocimene, marking the first reported identification of a neo-allo-ocimene synthase. Subsequently, we optimized the fermentation conditions and achieved a yield of 933.35 mg/L in a 1 L shake flask, which represents the highest reported titer of neo-allo-ocimene to date. These results reveal the molecular basis of neo-allo-ocimene synthesis in celery and provide a sustainable way to obtain this compound.